PERANCANGAN KAPAL PETI KEMAS (FULL CONTAINER) 180 TEUS RUTE PELAYARAN TJ. PERAK-BIMA (PP) DENGAN KECEPATAN 12 KNOT - Firdania Amelia Riyanto (2020)
The importance of inter-island shipping for Indonesia hardly requires confirmation. As an archipelagic country, the country depends a lot on shipping for domestic trade. The burden on the inter-island shipping industry that is inefficient on the economy can be demonstrated through an analogy with interisland tariffs (ie, trade taxes). Indonesia is best in relation to the unequal distribution of population and its resources. Two thirds of Indonesia's population is concentrated on the small but very fertile islands of Java and Bali. One third are scattered outside Java. This population distribution is reflected in inter-island trade patterns. Most food production and manufacturing are located in Java, and outside Java as exchangers for processed goods. With the development of science and technological advancements, an effective and efficient system for transporting goods by sea is developing, namely containers. Also supported Poros Maritim and Tol Laut that was put forward since the leadership of President Joko Widodo. Even though the use of containers is intended to reduce physical damage to goods that are inappropriate or inadvertent in containers can injure people when containers are managed or transported. In addition, serious and detrimental damage can occur to goods in the container or to other equipment. As well as the existence of a container system (container) the flow of trade is getting smoother between islands. As well as saving costs, time, fast and guaranteed security. Therefore the container system (container) is widely chosen for transportation of goods in the archipelago.